INTRODUCTION OF QUADRATIC EQUATIONS IN SOLVING PRACTICAL PROBLEMS OF PHYSICS - I.Makhmudov; M.Safarova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Mathematics is fundamental part of applied physics, in particular, mathematical quadratic equations are broadly implemented to reach the solutions of problems in physics therefore, it is highly recommended for physics teachers to understand and apply quadratic applications in order to huddle with physical problems in theory and practice.